2018
DOI: 10.1111/jcpe.12845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of life‐course family income trajectories on periodontitis: Birth cohort study

Abstract: Low and variable life course income increased the prevalence of moderate/severe periodontitis at age 31 years. The findings may inform programmes in identifying and targeting potentially at-risk groups during the life course to prevent periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
(35 reference statements)
0
16
0
2
Order By: Relevance
“…They suggest that any form of social mobility (either upward or downward) might positively impact adult perceptions of oral health, probably because mobile individuals seek to maximise their status [9,38]. The positive effect of downward social mobility found in this study contrasts with previous dental studies that reported a negative association between downward mobility and good oral health [11][12][13][14][15][16][17][18][19][20][21]. The fact that downward mobility was inversely associated with poor oral health implies that there will be more people with good oral health in the lower social class.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…They suggest that any form of social mobility (either upward or downward) might positively impact adult perceptions of oral health, probably because mobile individuals seek to maximise their status [9,38]. The positive effect of downward social mobility found in this study contrasts with previous dental studies that reported a negative association between downward mobility and good oral health [11][12][13][14][15][16][17][18][19][20][21]. The fact that downward mobility was inversely associated with poor oral health implies that there will be more people with good oral health in the lower social class.…”
Section: Discussionmentioning
confidence: 67%
“…The effect of social mobility on adult oral health has been investigated in several longitudinal studies, although most have focused on intergenerational mobility [11][12][13][14][15][16][17][18][19][20]. Only two previous studies have looked at intragenerational mobility in relation to oral health [12,21].…”
Section: Introductionmentioning
confidence: 99%
“…It was recorded that low standard of life increases the prevalence of periodontitis. 24 Another risk factor which plays a critical role in periodontitis is the different human habits. It was stated that poor oral hygiene habits increase the risk of periodontitis.…”
Section: Host Immune Response In Periodontitismentioning
confidence: 99%
“…Upwardly mobile income between childhood and adolescence improved dental care (Peres et al 2007). Later on, when 31 years old, Schuch et al (2018b) showed that adults belonging to low-and fluctuating-income trajectories from childhood to adulthood had twice as much the prevalence of periodontitis than in participants from stable high-income trajectories. The direct effect of early-life poverty on periodontitis in adulthood was also confirmed (Schuch et al 2018a).…”
Section: Is Low Individual/ Household-level Income Related To Worse Omentioning
confidence: 99%